Jahe Dalam Al-Quran dan Sains: Analisis Penafsiran M. Quraish Shihab Terhadap Q.S Al-Insan Ayat 17 Dalam Tafsir Al-Misbah - Putri, Alfi Liani; Andy, Safria; Utomo, Wahyu Wiji; Pemi, M. (Al-Wasathiyah: Journal of Islamic Studies, 2023)
Based on searches from various interpretations, it can be concluded that ginger, which is called Allah in the Qur'an in surah al-Insan verse 17, explains the features of ginger as a plant that is rich in properties and is also referred to as a herbal medicinal plant, food seasoning and as a ginger drink found in the world. and as a drink of heaven that is served to the believers of the inhabitants of heaven. The type of research used in this research is descriptive qualitative research. This study also uses the library research method or literature study with a data analysis approach and the interpretation methodology that the authors use in this study is the tahlili method. Where is the Tahlili approach interpreting surah al-Insan verse 17 concerning ginger as a drink of heaven in that verse. This research resulted that ginger is a spice plant that is often used as a traditional medicine which has properties for the body including providing a strong deterrent against various diseases and can improve the health condition of the body. In this discussion there is Tafsir Al-Misbah, where according to Quraish Shihab ginger in the Koran has been described as a drink for the inhabitants of heaven which gives warmth and pleasure to His faithful servants who are in heaven. From this writing, we can see that the pleasure provided by Allah SWT in heaven is far greater than the pleasures obtained in this world. Earthly pleasures are meaningless when compared to heavenly pleasures.